Challenges of Early Childhood Moral Education in the Family Based on the Al-Quran Perspective in the Era of Society 5.0 - Fitriana, Destri; Sari, Maya Novita; Aprillia, Triana; Wahyuni, Wahyuni (Proceeding International Conference on Religion, Science and Education, 2024)
Early childhood is a child whose age ranges from zero to six years. During this time, children experience rapid development. Therefore as parents have challenges in moral education in early childhood. With the progress of the times there are positive and negative impacts on the current generation. This is a concern for a nation and religion. Therefore, the purpose of this study is to find out the challenges of early childhood moral education carried out by families, based on the Koran in the era of society 5.0. This research method uses library research. Data collection through various literature quoted from the Al-Qur’an surah Al-Baqarah and Al-Luqman, also through books, journals, and other substances. So it can be concluded that the family plays an important role in the moral education of children by giving wise directions without being patronizing. The results of this research show that the role of the family in educating children’s morals in the era of society 5.0 has an important role. A good basic foundation for children’s moral development is teaching politeness through three magic sentences, namely, sorry, please and thank you. Based on the foundation of moral education from the Al-Quran perspective through the Al-Quran surah above, it can be concluded that in educating children’s morals, the most important thing to instill is the value of monotheism, the second is good civility towards parents and anyone else. Educating morals in children certainly cannot be separated from internal and external factors. These two factors are interrelated and must be controlled well, then there are three conditions that can influence a child’s morality, namely circumstances or situations, individual and social.